A Survey to Understand Parent/Caregiver and Children's Views on Devices Used for the Administration of Oral Pediatric Medicines in Japan - Jumpei Saito; Hidefumi Nakamura; Jennifer Walsh; Akimasa Yamatani; Smita Salunke (MDPI AG, 2022)
Administration devices are crucial for the correct dosing of medicines to children. In countries outside Japan, oral droppers and syringes are reported to be preferred for the administration of oral liquid medicines to neonates and infants, whilst spoons and cups are more frequently used for older children. However, in Japan the majority of oral medicines are powders and the use of dosing devices in each pediatric age group is not well known. This study was performed as an observational anonymous questionnaire survey on devices for oral medicines in children aged 10 to less than 18 years and parents/caregivers on behalf of children aged from birth to less than 18 years. The results from 336 respondents showed that powders were most frequently prescribed in children aged less than 10 years old followed by liquids. Unlike previous reports, droppers were most frequently used in patients less than 12 months old, while household spoons were most frequently used in older children. Oral syringes were perceived as easy to use, which was in line with previous studies. Further cross-regional multi-countries study for establishment the guidelines on the choice of device will be needed.